α-Fe2O3-mediated growth and carbon nanocoating of ultrafine SnO2 nanorods as anode materials for Li-ion batteries - Wang, Zhiyu (2013)
Bulk synthesis of SnO2 nanorods under acidic conditions has rarely been reported. In this work, ultrafine SnO2 nanorods with a diameter of less than 10 nm and a length of 50–100 nm have been synthesized by an interesting α-Fe2O3-mediated hydrothermal method under strongly acidic conditions. It has been found that the formation of SnO2 nanorods is induced by the α-Fe2O3 substrate due to good compatibility of the two crystal lattices. The α-Fe2O3 substrate is dissolved under acidic conditions, leading to the formation of pure SnO2 nanorods. After surface coating with a layer of amorphous carbon, the resulting carbon-coated SnO2 nanorods are evaluated as high-capacity anode materials for lithium-ion batteries. Remarkably, they exhibit greatly improved cycling stability with a high capacity of around 800 mA h g−1 at 0.2 C and satisfactory performance even at higher current rates of 0.5–1 C within 50 cycles. The excellent electrochemical performance is attributed to the unique one-dimensional nanostructure and the carbon nanocoating.